(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2022)
Zestoretic, a combination of lisinopril and hydrochlorothiozide used as anti-hypertension drug prescribed even during pregnancy. Role of zestoretic on the developmental landmars of young ones exposed prenatally are yet to be established. Hence, the present investigation initiated to test in Wistar rats. Three groups of inseminated female rats were oral gavaged with zestoretic (lisinopril varied concentrations + hydrochlorothiozide 12.5mg) 25, 50 and 100 mg/Kg body weight (BW) on gestation days 7, 9, 11 and 13, whereas control group with double distilled water. Clinical toxicity found in few dams from 50 and 100 mg/Kg BW received rat shown aggressive behavior during experimentation. The developmental landmarks, such as pinna attachment, ear opening, fur development, eye opening, upper and lower incisor eruption, crown rump length, vaginal opening and testes descend were measured periodically on their postnatal days in all the young ones. The number of live pups in zestoretic 50, 100 mg/Kg BW administered females are significantly less (P